Clinical Utility of a Multiplex PCR Panel (BioFire Joint Infection®) in the Adjustment of Empiric Antimicrobial Therapy: Experience in Pediatric Osteoarticular Infections - Clara Udaondo; Rosa María Alcobendas Rueda; Blanca Diaz-Delgado; Agustin Remesal; Inmaculada Quiles-Melero; Cristina Calvo (MDPI AG, 2024)
Background/Objectives: This study aims to evaluate the impact of the PCR multiplex panel (BioFire JI®) on the diagnosis and management of pediatric osteoarticular infections. Methods: This retrospective study analyzed data from pediatric patients diagnosed with osteoarticular infections between January 2023 and April 2024. The effectiveness of the PCR multiplex panel in identifying pathogens was compared with traditional culture methods. Results: In total, 50 patients were identified (66.6% male, 74% under 3 years of age). They were diagnosed as follows: septic arthritis in 46%, osteomyelitis in 26%, and septic osteoarthritis in 22%. An identifiable agent was isolated by conventional culture in 22 cases (44%). Kingella kingae was the predominant pathogen identified, accounting for 50% of cases (11/22), followed by Staphylococcus aureus (9/22). The BioFire JI® Panel PCR demonstrated a sensitivity of 93%, with a specificity of 63% when evaluated against synovial fluid culture as the reference standard. The panel identified seven additional pathogens not detected by conventional culture methods: 2/9 MSSA (22%), 1/1 S. pyogenes (100%), and 4/11 K. kingae (37%), increasing the yield by 14%. The rapid identification of pathogens facilitated timely and targeted therapeutic interventions. Conclusions: The PCR multiplex panel (BioFire JI®) improved the diagnosis of pediatric osteoarticular infections.